MANAGEMENT ANXIETY LEVEL BY USING LEMONGRASS AROMATHERAPY ON RESIDENTS OF RT 7 RW 4 KAPASARI VILLAGE SEMAMPIR DISTRICT SURABAYA - Ramadhani, Dwi Yuniar (Journal of Health Community Service, 2022)
The Covid-19 pandemic affects people’s psychology, particularly the incorrect information about covid-19 that causes worry, stress and anxiety. This study aims to manage anxiety levels by using lemongrass aromatherapy. Community service activities were carried out in the RT 7 RW 4 Kapasari Village area, with as many as 34 residents. The activities carried out were about health education and the manufacture of lemongrass aromatherapy. While the health condition used media in the form of leaflets. Activities were carried out online and offline. Measuring instruments used was Anxiety Scale (CAS). The results showed a change in anxiety levels, namely not anxiety as much as 64.7% and anxiety as much as 35.3%. Lemongrass contents can provide a sense of relaxation to reduce anxiety. Proper anxiety management during the Covid-19 pandemic can increase immunity and provide serenity so that people can have a good And healthy life.